Using Multiplexed Assays of Oncogenic Drivers in Lung Cancers to Select Targeted Drugs - Kris, Mark G; Johnson, Bruce E; Berry, Lynne D; Kwiatkowski, David J; Iafrate, A. John; Wistuba, Ignacio I; Varella-Garcia, Marileila; Franklin, Wilbur A; Aronson, Samuel L; Su, Pei-Fang; Shyr, Yu; Camidge, D. Ross; et al. (JAMA : the journal of the American Medical Association, 2014)
IMPORTANCE Targeting oncogenic drivers (genomic alterations critical to cancer development and maintenance) has transformed the care of patients with lung adenocarcinomas. The Lung Cancer Mutation Consortium was formed to perform multiplexed assays testing adenocarcinomas of the lung for drivers in 10 genes to enable clinicians to select targeted treatments and enroll patients into clinical trials. OBJECTIVES To determine the frequency of oncogenic drivers in patients with lung adenocarcinomas and to use the data to select treatments targeting the identified driver(s) and measure survival. DESIGN, SETTING, AND PARTICIPANTS From 2009 through 2012, 14 sites in the United States enrolled patients with metastatic lung adenocarcinomas and a performance status of 0 through 2 and tested their tumors for 10 drivers. Information was collected on patients, therapies, and survival. INTERVENTIONS Tumors were tested for 10 oncogenic drivers, and results were used to select matched targeted therapies. MAIN OUTCOMES AND MEASURES Determination of the frequency of oncogenic drivers, the proportion of patients treated with genotype-directed therapy, and survival. RESULTS From 2009 through 2012, tumors from 1007 patients were tested for at least 1 gene and 733 for 10 genes (patients with full genotyping). An oncogenic driver was found in 466 of 733 patients (64%). Among these 733 tumors, 182 tumors (25%) had the KRAS driver; sensitizing EGFR, 122 (17%); ALK rearrangements, 57 (8%); other EGFR, 29 (4%); 2 or more genes, 24 (3%); ERBB2 (formerly HER2), 19 (3%); BRAF, 16 (2%); PIK3CA, 6 (<1%); MET amplification, 5 (<1%); NRAS, 5 (<1%); MEK1, 1 (<1%); AKT1, 0. Results were used to select a targeted therapy or trial in 275 of 1007 patients (28%). The median survival was 3.5 years (interquartile range [IQR], 1.96-7.70) for the 260 patients with an oncogenic driver and genotype-directed therapy compared with 2.4 years (IQR, 0.88-6.20) for the 318 patients with any oncogenic driver(s) who did not receive genotype-directed therapy (propensity score–adjusted hazard ratio, 0.69 [95% CI, 0.53-0.9], P = .006). CONCLUSIONS AND RELEVANCE Actionable drivers were detected in 64% of lung adenocarcinomas. Multiplexed testing aided physicians in selecting therapies. Although individuals with drivers receiving a matched targeted agent lived longer, randomized trials are required to determine if targeting therapy based on oncogenic drivers improves survival. TRIAL REGISTRATION clinicaltrials.gov Identifier: NCT01014286.